Principles of equity - Kames, Henry Home, Lord, 1696-1782 (Kames, Henry Home, Lord, 1696-1782. Works. 2005., 2014)
"Henry Home, Lord Kames, was the complete "Enlightenment man," concerned with the full spectrum of human knowledge and its social use. However, as a lawyer and, after 1752, as a judge on the Court of Session in Edinburgh, he made many of his most distinctive contributions through his works on the nature of law and legal development. Principles of Equity, first published in 1760, is considered his most lasting contribution to jurisprudence and is still cited. In his jurisprudence, Kames specifically sought to explain the distinction between the nature of equity and common law and to address related questions, such as whether equity should be bound by rules and whether there should be separate courts of law and equity. Beginning with a general introduction on the rise and nature of equity, Principles of Equity is divided into three books. The first two, "theoretical," books examine the powers of a court of equity as derived from justice and from utility, the two great principles Kames felt governed equity. The third book aims to be more practical, showing the application of these powers to several subjects, such as bankrupts. Principles of Equity is significant as an example of the approach of an Enlightenment thinker to practical legal questions and as an early attempt to reduce law to principles. There is evidence that this book was well known in the formative years of the United States and that both Benjamin Franklin and Thomas Jefferson were familiar with Kames's treatise. Henry Home, Lord Kames (1696-1782), one of the leaders of the Scottish Enlightenment, was a judge in the supreme courts of Scotland and wrote extensively on morals, religion, education, aesthetics, history, political economy, and law, including natural law. His most distinctive contribution came through his works on the nature of law, where he sought to combine a philosophical approach with an empirical history of legal evolution. Michael Lobban is Professor of Legal History at Queen Mary, University of London. Knud Haakonssen is Professor of Intellectual History and Director of the Centre for Intellectual History at the University of Sussex, England"--